Islamic Participation: A Study of Community Participation in Village Development from an Islamic Economic Perspective - Mutiara, Nisa (Prosiding Seminar; 2021: 2021 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.57, 2022)
Village development after the enactment of Law Number 6 of 2014 or the Village Law regulates community participation in village development in Indonesia, starting from planning, implementing, monitoring and utilizing development. The majority of the villagers are Muslim. Welfare (falah) in Islam can be achieved by maintaining Maqashid Shari'ah, which consists of guarding religion, soul, mind, lineage, and property. This study aims to analyze the role of the village community as a society that upholds Islamic values ​​as a source of collective values ​​in village development, to improve welfare (falah) after the enactment of Law Number 6 of 2014. The research method used in this study is the method of qualitative research with a case study approach. In-depth interviews were conducted with 17 informants. Based on the results of the study, there are 4 (four) Main Principles of Islamic Participation in village development, namely monotheism, trustworthiness, amar ma'ruf nahi munkar and mardhatillah.